The Reality of Knowledge Management in Organizations: Greater Amman Municipality Experience - Boualleg, Nawal; Djoual, Maroua; Bensaada, Abdelkader (Social Empowerment Journal, 2020)
The modernity of knowledge management as one of the hour topics, imposed the necessity to address this research and to give him enough attention, by taking cognizance of its conceptual framework and trying to address the most important processes and strategies of knowledge management, in addition to explaining the motives that led the Greater Amman Municipality to adopt this concept, highlighting the practical steps taken by this municipality in establishing knowledge management as one of the criteria of excellence that it has set in its mission. The results showed that the Greater Amman Municipality followed a set of practical stages in order to integrate knowledge management in the daily operations of the organization, from the awareness stage to ensure commitment to the planning and implementation stage, disseminate knowledge, and then ensure effective communication between the parties involved in this experiment. The gradual integration of knowledge is essential in order to exploit the implicit and explicit knowledge found in the organization, which enhances its competitiveness and excellence.